Kesalahan Penggunaan EYD terhadap Paragraf Eksposisi - Poni Ernis (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2020)
The purpose of this study is to analyze the use of EYD in the exposition paragraph. This type of research is qualitative research using descriptive methods. Based on the results of the study, the errors in using EYD for exposition paragraphs are grouped into three parts, namely capital letters, preposition and punctuation. Writing capital letters results in 279 cases of error, the use of prepositions of data results in 24 cases of errors, while the use of punctuation is further divided into the use of a period (.) And the use of a comma (,), the use of a period of data results in 26 cases of errors, while the use of commas obtained data results as many as 36 cases of errors. Thus it can be concluded that the misuse of EYD was caused by students' lack of understanding of the writing procedure according to the EYD system. Keywords: Exposition Text, EYD Usage Error